2018
DOI: 10.1093/jn/nxy032
|View full text |Cite
|
Sign up to set email alerts
|

Cholecalciferol Supplementation Promotes Bone Turnover in Chinese Adults with Vitamin D Deficiency

Abstract: Daily supplementation with 2000 IU cholecalciferol for 20 wk may promote bone formation in Chinese adults with vitamin D deficiency. More studies are needed to elucidate the potential clinical implications of BTMs. This trial was registered at clinicaltrials.gov as NCT01998763.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
0
13
0
2
Order By: Relevance
“…27 With regard to BTMs, only few studies have investigated the relation between vitamin D 3 administration and P1NP and CTX-1 and especially data from rat studies are limited. While long-term human studies involving vitamin D supplementation have shown consistent increases in 25-hydroxy vitamin D 3 , but varying effects on BTMs, 28–30 results from acute studies involving higher doses of vitamin D 3 show a response on P1NP and CTX-1 within 4 hours 31 and a peak around day 2–3. 32 This could imply that measurements of BTMs are most relevant within the first few days of vitamin D administration, which should be considered for future studies.…”
Section: Resultsmentioning
confidence: 98%
“…27 With regard to BTMs, only few studies have investigated the relation between vitamin D 3 administration and P1NP and CTX-1 and especially data from rat studies are limited. While long-term human studies involving vitamin D supplementation have shown consistent increases in 25-hydroxy vitamin D 3 , but varying effects on BTMs, 28–30 results from acute studies involving higher doses of vitamin D 3 show a response on P1NP and CTX-1 within 4 hours 31 and a peak around day 2–3. 32 This could imply that measurements of BTMs are most relevant within the first few days of vitamin D administration, which should be considered for future studies.…”
Section: Resultsmentioning
confidence: 98%
“…In total, 17 studies involving intervention with vitamin D supplements were identified, which are presented in Table 1 . Participants’ (n = 4482) mean age varied from 43 to 75 years, and the durations of the studies ranged from 8 weeks to 3 years [ 18 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. In seven studies, only females were included [ 18 , 32 , 33 , 34 , 35 , 36 , 37 ], in two studies, only males were included [ 38 , 39 ], while in the remaining eight studies, both sexes were included [ 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, in one study involving Chines adults, vitamin D supplementation increased serum levels of bone alkaline phosphatase, but did not affect PINP and CTX levels. However, in subjects whose 25(OH)D concentration exceeded 30 ng/ml, an increase of CTX levels was observed [21]. Conversely, it has been demonstrated that improved vitamin D status in younger postmenopausal women leads to a signi cant reduction in serum CTX and PINP levels [22].…”
Section: Response To Want and Vitamin Dmentioning
confidence: 99%